Investing in Parenthood - Blustein, Jeffrey (The Hastings Center report, 2018)
The recent child custody case Weisberger v Weisberger raises a number of ethical issues concerning the rights and responsibilities of parents. Chavie Weisberger, thirty-five, and her husband, both members of an ultraorthodox Hasidic community, appeared before a religious court in 2008 to obtain a divorce. There are two sharply contrasting legal rulings in this case. Setting aside the legally significant fact that Chavie had signed the divorce agreement with the clause requiring her to raise her children Hasidic, which decision is ethically more defensible and why? Were Chavie's parental rights violated when the court removed her children from her care? Should her ex-husband have been awarded full custody on the ground that this was in the children's best interest, and is this the right standard to use in making custody decisions? What parental responsibilities did Chavie and her ex-husband have, and were they satisfactorily discharging them? A theory of the moral foundations of parenthood should provide answers to these questions among others. Joseph Millum, in his excellent new book The Moral Foundations of Parenthood, does this and more. His theory encompasses accounts of the foundation and content of parental rights and responsibilities, the acquisition of parental responsibilities, and the standards governing parental decision-making.